Knowledge and Practice on management of Drowning in a Rural Community of Bangladesh (KYAMC Journal, 2025)
Background: Drowning is a significant public health issue in Bangladesh. The World Health Organization (WHO) reports that drowning is one of the leading causes of death among children aged 1 to 4 in Bangladesh. Contributing factors include a lack of swimming skills, inadequate supervision, and the proximity of residences to open water sources. Objective: This study was designed to assess the knowledge and practice on management of drowning in rural community.Materials and methods: This descriptive cross-sectional study was conducted in Jamtoyel, Ajugora and Subornosara in Belkuchi upazila under Sirajganj District from January to December 2019. Convenience sampling was adopted to select 350 respondents. Data were collected through face-to-face interview with a semi-structured questionnaire. Collected data were checked, cleaned, entered into computer and analyzed using SPSS version 23.Results: Among the respondents, 76.3% were male, 39.7% were businessmen, and 21.1% were housewives. About 80% had some form of education. Most (96.3%) of the respondents were Muslims, and mean monthly income was Taka 14,785.7 taka with SD ±7816.2. Majority (74.0%) had poor knowledge, 23.1% had average knowledge, and only 2.9% had good knowledge regarding the management of drowning. About practice of managing drowning victims, it was observed that all of the them who participated in management had poor practice, with none demonstrating average or good practice.Conclusion: Efforts to mitigate this crisis include community education programs, swimming lessons, and the construction of barriers around hazardous water bodies, but much work remains to effectively address and reduce drowning rates in the country.KYAMC Journal. 2024; 15(02): 66-72